2020
DOI: 10.1097/md.0000000000020888
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of prognostic value of the neutrophil-to-lymphocyte ratio in early miscarriages

Abstract: This study aims to identify prognostic value of neutrophil-to-lymphocyte ratio (NLR) in early miscarriages. A total of 260 pregnant women with vaginal spotting were recruited from the Department of Obstetrics and Gynecology of the Kyung Hee Medical Center from January 1, 2011, and December 31, 2018. Venous samples were obtained from the women for measurements of platelet-to-lymphocyte ratio, lymphocyte-to-monocyte ratio, and NLR. All the patients were in < 14 gestational weeks of their pregnancy. Eighty-four p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…3,4 The physical and emotional health of a woman can be severely impacted by a miscarriage, and many studies have been conducted on the prediction and prevention. 5,6 A novel index called the systemic immune-inflammation index (SII) was developed based on the peripheral lymphocyte, neutrophil, and blood platelet counts evaluated for the prediction of adverse pregnancy outcomes. 7 In this study, we evaluate the clinical significance of the SII values of patients who had miscarriages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The physical and emotional health of a woman can be severely impacted by a miscarriage, and many studies have been conducted on the prediction and prevention. 5,6 A novel index called the systemic immune-inflammation index (SII) was developed based on the peripheral lymphocyte, neutrophil, and blood platelet counts evaluated for the prediction of adverse pregnancy outcomes. 7 In this study, we evaluate the clinical significance of the SII values of patients who had miscarriages.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal age, ethnic origin, a very low or very high body mass index (BMI), stress, infection, drug use, smoking, and alcohol consumption have also been associated with miscarriage 3,4 . The physical and emotional health of a woman can be severely impacted by a miscarriage, and many studies have been conducted on the prediction and prevention 5,6 . A novel index called the systemic immune‐inflammation index (SII) was developed based on the peripheral lymphocyte, neutrophil, and blood platelet counts evaluated for the prediction of adverse pregnancy outcomes 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the study of Kim (17) , revealed significantly lower NLR in patients with missed abortion when compared to patients with threatened abortion. However, Biyik et al (18) reported significantly higher NLR in missed abortion group as compared to normal pregnancy group (P 0.038).…”
Section: Discussionmentioning
confidence: 85%
“…Biyik et al 35 showed that NLR and PLR values were higher in the missed miscarriage group than in the healthy pregnant women group. Kim et al 36 showed that NLR was the prognostic factor for distinguishing between the missed abortion and threatened abortion. In contrast to these studies, we found that the NLR and PLR values were similar in missed miscarriage and normal pregnancy group ( p > 0.05).…”
Section: Discussionmentioning
confidence: 99%